If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.7x + 2.8 = 19 Reorder the terms: 2.8 + 2.7x = 19 Solving 2.8 + 2.7x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.8' to each side of the equation. 2.8 + -2.8 + 2.7x = 19 + -2.8 Combine like terms: 2.8 + -2.8 = 0.0 0.0 + 2.7x = 19 + -2.8 2.7x = 19 + -2.8 Combine like terms: 19 + -2.8 = 16.2 2.7x = 16.2 Divide each side by '2.7'. x = 6 Simplifying x = 6
| -17=3+5 | | 9x-12+2x=11x+6 | | d-2.94=1.36 | | 2(3x+4)-3=6x+5 | | -5+9=21 | | 3m-10=24m-5 | | x/18+x/3 | | 8(y+6)+y=4(y+5)+2 | | 1/31/2x/3 | | -4(3x-4)+1=-12x+17 | | 5x+4=12+5x | | 2x-3+4x-8=13 | | 5*29= | | 7x-8y=64 | | 11*15= | | 2(x-4)(x-3)=x-13 | | 9x+6=9(x-3) | | X+4/3=x-8/5 | | X/4-3=-4 | | -8-3+6*2= | | 3z=14-29 | | 3(3m-2)+10=3(m-4)-3 | | 23x-7-14x+4=25x-4-16x+12 | | (5a-2)(7a+3)=0 | | 0.14(y-6)+0.04y=0.08y-0.1 | | 5-5(-5-7/-6)-13 | | -4(4x+1)=-52 | | 6x^2=10x+4 | | 3a-6x+4-12a+3x= | | 3(x+2)=-2(x-8) | | x(1-x)=25(x-1) | | 4-(-2n+3)=44 |